The ISVsa3-ORF2-abh-tet(X4) circular intermediate-mediated transmission of tigecycline resistance in Escherichia coli isolates from duck farms - Jiang, Chao; Yang, Jie; Xiao, Gang; Xiao, Ning; Hu, Jie; Yang, Yi; Sun, Zhiliang (Frontiers in Cellular and Infection Microbiology, 2024)
Tigecycline is a last-resort drug used to treat serious infections caused by multidrug-resistant bacteria. tet(X4) is a recently discovered plasmid-mediated tigecycline resistance gene that confers high-level resistance to tigecycline and other tetracyclines. Since the first discovery of tet(X4) in 2019, it has spread rapidly worldwide, and as a consequence, tigecycline has become increasingly ineffective in the clinical treatment of multidrug-resistant infections. In this study, we identified and analyzed tet(X4)-positive Escherichia coli isolates from duck farms in Hunan Province, China. In total, 976 samples were collected from nine duck farms. Antimicrobial susceptibility testing and whole-genome sequencing (WGS) were performed to establish the phenotypes and genotypes of tet(X4)-positive isolates. In addition, the genomic characteristics and transferability of tet(X4) were determined based on bioinformatics analysis and conjugation. We accordingly detected an E. coli strain harboring tet(X4) and seven other resistance genes in duck feces. Multi-locus sequence typing analysis revealed that this isolate belonged to a new clone, and subsequent genetic analysis indicated that tet(X4) was carried in a 4608-bp circular intermediate, flanked by ISVsa3-ORF2-abh elements. Moreover, it exhibited transferability to E. coli C600 with a frequency of 10-5. The detection of tet(X4)-harboring E, coli strains on duck farms enhances our understanding of tigecycline resistance dynamics. The transferable nature of the circular intermediate of tet(X4) contributing to the spread of tigecycline resistance genes poses a substantial threat to healthcare. Consequently, vigilant monitoring and proactive measures are necessary to prevent their spread.